2015
DOI: 10.3892/mmr.2015.4501
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors promote neurogenesis in the neonatal rat subventricular zone following hypoxic-ischemic injury

Abstract: Evidence suggests the involvement of N-methyl-D-aspartate receptors (NMDAR) in the regulation of neurogenesis. Functional properties of NMDAR are strongly influenced by the type of NR2 subunits in the receptor complex. NR2A- and NR2B-containing receptors are expressed in neonatal fore-brain regions, such as the subventricular zone (SVZ). The aim of the present study was to examine the effect of the protein expression of hypoxic-ischemic injury NMDAR subunits 2A and 2B in the SVZ of neonatal rats. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Studies have shown that neonatal hypoxic-ischemic injury is correlated to NMDA receptor-mediated excitotoxicity ( Johnston et al, 2002 ; Wu et al, 2017 ). Furthermore, it has also been proven that after 6 h of hypoxia ischemia, the expression of GluN2A significantly decreases, while the expression of GluN2B exhibits an opposite trend, which reaches a maximum at 24 h after hypoxic ischemia ( Lai et al, 2016 ). This suggests that GluN2A and GluN2B might play different roles in neonatal HIE.…”
Section: The Nmda Receptor Is Involved In Neonatal Hypoxic-ischemic Ementioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that neonatal hypoxic-ischemic injury is correlated to NMDA receptor-mediated excitotoxicity ( Johnston et al, 2002 ; Wu et al, 2017 ). Furthermore, it has also been proven that after 6 h of hypoxia ischemia, the expression of GluN2A significantly decreases, while the expression of GluN2B exhibits an opposite trend, which reaches a maximum at 24 h after hypoxic ischemia ( Lai et al, 2016 ). This suggests that GluN2A and GluN2B might play different roles in neonatal HIE.…”
Section: The Nmda Receptor Is Involved In Neonatal Hypoxic-ischemic Ementioning
confidence: 99%
“…Hence, they might also play similar roles in HIE. Although most researches have indicated the pro-death role of GluN2B in HIE, there is also evidence that GluN2B could protect neurons against apoptosis during development ( Martel et al, 2009 ; Lai et al, 2016 ). Since the GluN2B-containing NMDA receptor is the dominant subtype in early development, it remains to be determined whether GluN2B plays dual roles in HIE.…”
Section: The Nmda Receptor Is Involved In Neonatal Hypoxic-ischemic Ementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these clinical benefits, cognitive enhancements have been observed in declarative and working memory and other cognitive functions in healthy subjects ( Jensen et al ., 2016 ; Veroniki et al ., 2016 ). In this case, potential natural products or their active compounds may promote neurogenesis-associated cell proliferation, migration, differentiation, apoptosis, and synaptogenesis via modulation of NMDARs in the central nervous system (CNS) ( Kim and Oh, 2013 ; Lai et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%